VERSATILITY OF TENSOR FASCIA LATA FLAP FOR RECONSTRUCTION OF GROIN DEFECTS - Anwar, Saira; Waqas Sami; Faisal Akhlaq Ali Khan; Sumaira Sattar; Saba Kiran; Sindhu Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: The evolution of reconstructive surgery techniques has significantly improved the management of soft tissue defects across various anatomical regions. In 1972, McGregor et al. devised a pivotal method for generating a flap to cover hand defects. The benefits of this technique, which include a larger skin surface without the need for microsurgery and yielding an easily concealed donor site scar, quickly became a cornerstone in the field, evidencing its widespread acceptance and application. Objective was to compare outcomes such as wound infection, skin flap necrosis and hospital stay between primary closure and tensor fascia lata flap for the reconstruction of groin defects among patients presenting at tertiary care hospital, Karachi, Pakistan. Methods: It was a prospective observational study carried out at the Department of plastic surgery, Dow University of Health Sciences, Civil hospital, Karachi, Pakistan from 23rd August 2023 to 25th January 2024. Patients who had groin defects after trauma or excision of lymph node of age 20-80 years of either gender were included and divided into two groups. Group A (n=30) had patients who had primary wound closure, while Group B (n=30) had patients who underwent a tensor fascia lata flap procedure for wounds coverage. Both groups were compared in terms of wound infection, skin flap necrosis, and hospital stay following surgery after 4 weeks. Data was analyzed using SPSS version 23. Results: The overall average age of participants in the study was 35.7±11.18 years. Of 73.3% participants were male and 26.7% were female. Group B (TFL flap reconstruction) demonstrated significantly lower rates of wound infection (p=0.001) and skin flap necrosis (p=0.001) compared to Group A (primary closure). Additionally, the average hospital stay was significantly shorter for Group B than Group A (p=0.001). Conclusion: TFL flap reconstruction for groin defects significantly reduces postoperative complications, including wound infection and skin flap necrosis, and shortens hospital stays compared to primary closure.